Legislative tax announcements and GDP - Hayo, Bernd,Mierzwa, Sascha (Philipps-University Marburg, School of Business and Economics, 2021)
We study the announcement effect of legislated tax changes on GDP in the US, Germany, and the UK. Using, as the shock of interest, narratively identified information (Romer & Romer, 2009) about future tax changes at the quarter of their introduction to the legislative body, we analyse the dynamic results of Local Projections (Jordà, 2005). We find hetero-geneous effects across the three countries: economic activity declines (increases) in the US (the UK), but remains unaffected in Germany. When allowing the responses to vary over the business cycle, we find evidence that US GDP drops regardless of the business cycle, whereas UK GDP rises only during non-recessionary times. We find significant effects for German GDP too: it rises (drops) during recessionary (non-recessionary) times. In general, consumption, investment, and employment follow in the path of GDP.
10419/244363
Keywords: Graue Literatur; Fiscal policy; tax policy; legislated tax changes; announcement effect; state dependence; United States; Germany; United Kingdom; Local Projections; narrative approach